Influence of Temperature Variations on Grapevine Phenology - Kimani, Bonface Kimani (American Journal of Agriculture, 2024)
Purpose: The aim of the study was to analyze the influence of temperature variations on grapevine phenology. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Temperature variations strongly impact grapevine phenology, with warmer conditions advancing growth stages and cooler temperatures causing delays. This has direct consequences for grape quality and wine production, emphasizing the importance of temperature monitoring for vineyard management and adapting to climate changes. Implications to Theory, Practice and Policy: Phenological response theory, climate change theory and bioclimatic model theory may be used to anchor future studies on analyzing the influence of temperature variations on grapevine phenology. Develop and disseminate practical guidelines for vineyard managers and growers to adapt to temperature variations effectively. Advocate for policies that support climate-resilient viticulture practices. Encourage government agencies to incentivize research, development, and adoption of adaptive strategies within the wine industry.